Associate aPSYCHOLOGICAL DIFFICULTIES ARISING DURING THE PROCESS OF FAMILY LIFE ADAPTATION FOR CHILDREN WITH DISABILITIESProfessor of Banking and Finance Academy, PhD. (Innovate Conferences, 2025)
This thesis examines the major psychological difficulties faced by children with disabilities during their adaptation to family life. It explores issues such as low self-esteem, anxiety, social isolation, and strained family relationships. The paper also highlights the importance of emotional support from family members and the role of psychological services in facilitating healthy adjustment for children with disabilities.